Delays in Auditory Processing Identified in Preschool Children with FASD - Stephen, Julia M.; Kodituwakku, Piyadasa W.; Kodituwakku, Elizabeth L.; Romero, Lucinda; Peters, Amanda M.; Sharadamma, Nirupama M.; Caprihan, Arvind; Coffman, Brian A. (Alcoholism, clinical and experimental research, 2012)
Background Both sensory and cognitive deficits have been associated with prenatal exposure to alcohol; however, very few studies have focused on sensory deficits in preschool‐aged children. As sensory skills develop early, characterization of sensory deficits using novel imaging methods may reveal important neural markers of prenatal alcohol exposure. Methods Participants in this study were 10 children with a fetal alcohol spectrum disorder (FASD) and 15 healthy control (HC) children aged 3 to 6 years. All participants had normal hearing as determined by clinical screens. We measured their neurophysiological responses to auditory stimuli (1,000 Hz, 72 dB tone) using magnetoencephalography (MEG). We used a multidipole spatio‐temporal modeling technique to identify the location and timecourse of cortical activity in response to the auditory tones. The timing and amplitude of the left and right superior temporal gyrus sources associated with activation of left and right primary/secondary auditory cortices were compared across groups. Results There was a significant delay in M100 and M200 latencies for the FASD children relative to the HC children (p = 0.01), when including age as a covariate. The within‐subjects effect of hemisphere was not significant. A comparable delay in M100 and M200 latencies was observed in children across the FASD subtypes. Conclusions Auditory delay revealed by MEG in children with FASDs may prove to be a useful neural marker of information processing difficulties in young children with prenatal alcohol exposure. The fact that delayed auditory responses were observed across the FASD spectrum suggests that it may be a sensitive measure of alcohol‐induced brain damage. Therefore, this measure in conjunction with other clinical tools may prove useful for early identification of alcohol affected children, particularly those without dysmorphia.